Evaluation of the practicum in postgraduate training in communication studies from a professional and student orientation - Campillo Alhama, Conchi; Quiler Soler, María del Carmen (Historia y Comunicación Social, 2014)
Evaluative research stands as a necessary tool to reorient teaching proposals developed with students. Through this study evaluates the achievement of the objectives related to the professional practice of students in the Master of Creative Industries Communication during the 2011-2012 academic year at the University of Alicante. The results obtained allow a reflection on future directions that we give this educational intervention process, reinforcing the learning objectives less consolidated.
Keywords: Communication; Creative Industries; Practicum; European Higher Education Area; Evaluation.